Environment and development in Bangladesh - Rahman, A. Atiq. (Dhaka, Bangladesh : University Press, 1994)
Contributed articles.
Includes bibliographical references.
Keywords: Environmental policy -- Bangladesh; Human ecology -- Bangladesh